1999
DOI: 10.21273/jashs.124.6.719
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Nitrogen Partitioning, Recovery, and Losses in Bermudagrass Receiving Soluble Sources of Labeled 15Nitrogen

Abstract: ADDITIONAL INDEX WORDS. Turfgrass nutrition, Cynodon dactylon 'Tifgreen', photoperiod, irradiance, temperature ABSTRACT. Two greenhouse studies were conducted to trace the fate of fertilizer N in hybrid bermudagrass [Cynodon dactylon (L.) Pers. x C. transvaalensis Burtt-Davy 'Tifgreen'], and to estimate total plant N recovery and losses. The first experiment was performed during winter, with artificial light supplementing natural light to provide a photoperiod of 13.6 to 13.8 hours. The second experiment was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Reports of improved shoot color (Glinski et al, 1990), shoot growth (Picchioni and Quiroga-Garza, 1999), and/ or NUP (Bailey, 1999;Bloom et al, 1992;Bowman and Paul, 1988) by NH 4 -N fertilization have addressed whole plant responses. Whole-plant studies that directly measured greater NH 4 uptake from NH 4 -N fertilization than NO 3 uptake from NO 3 -N fertilization report either increased (Bailey, 1999;Bloom et al, 1992), indiscernible (Picchioni and Quiroga-Garza, 1999), or decreased root growth response. Bowman and Paul (1988) measured 8% greater perennial ryegrass root mass accumulation with NO 3 -N treatment than by NH 4 -N treatment during the 48-h period immediately following N application.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports of improved shoot color (Glinski et al, 1990), shoot growth (Picchioni and Quiroga-Garza, 1999), and/ or NUP (Bailey, 1999;Bloom et al, 1992;Bowman and Paul, 1988) by NH 4 -N fertilization have addressed whole plant responses. Whole-plant studies that directly measured greater NH 4 uptake from NH 4 -N fertilization than NO 3 uptake from NO 3 -N fertilization report either increased (Bailey, 1999;Bloom et al, 1992), indiscernible (Picchioni and Quiroga-Garza, 1999), or decreased root growth response. Bowman and Paul (1988) measured 8% greater perennial ryegrass root mass accumulation with NO 3 -N treatment than by NH 4 -N treatment during the 48-h period immediately following N application.…”
Section: Resultsmentioning
confidence: 99%
“…3 C. transvaalensis Burtt-Davey cv. Tifgreen] fertilized with (NH 4 ) 2 SO 4 contained 9% more relative N in leaf clippings than bermudagrass fertilized with NH 4 NO 3 (Picchioni and Quiroga-Garza, 1999). Bloom et al (1992) and Bowman and Paul (1988) reported enhanced assimilation of reduced N by barley (Hordeum vulgare L.) and perennial ryegrass (Lolium perenne L.) respectively, when fertilized with NH 4 -N sources compared to NO 3 -N sources.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typical N recovery by aboveground plant tissue is generally assumed to be ~50%; however, studying a Cynodon hybrid receiving ammonium nitrate (AN), Impithuksa and Blue (1985) reported much smaller N recovery (15-35%), suggesting that forage N use efficiency likely varies according to soil characteristics, rainfall distribution, and N application level. Conversely, Picchioni and Quiroga-Garza (1999) reported that N losses, measured as 15 N, were not influenced by N fertilizer source and that increased N levels decreased N recovery. Conversely, Picchioni and Quiroga-Garza (1999) reported that N losses, measured as 15 N, were not influenced by N fertilizer source and that increased N levels decreased N recovery.…”
mentioning
confidence: 95%
“…In a 3-yr study that evaluated 'Coastal' bermudagrass [Cynodon dactylon (L.) Pers] responses to different N sources on a sandy soil, Burton and Jackson (1962) reported that surface application of AN resulted in 26% greater N recovery than urea. Conversely, Picchioni and Quiroga-Garza (1999) reported that N losses, measured as 15 N, were not influenced by N fertilizer source and that increased N levels decreased N recovery. A similar pattern was also reported by Dillard et al (2015).…”
mentioning
confidence: 95%